Comparison of the influence of cationic polysaccharides on the stability properties of montmorillonite suspensions in the presence of sodium dodecyl sulphate. (15th February 2022) - Godek, E.; Grządka, E.; Maciołek, U.
Abstract: The mixtures of cationic cellulose (CC) or cationic guar gum (CGG) with the anionic sodium dodecyl sulfate surfactant (SDS) were used as stabilizers for the aqueous suspensions of montmorillonite (Mt). The stabilization processes and the stabilization mechanism were investigated using the UV-VIS. The obtained results show that both polysaccharides can be used as stabilizers of the water suspensions of montmorillonite due to the effective adsorption of CC and CGG with or without SDS on the Mt. surface. To obtain complete information on the studied systems, the additional measurements of the surface tension, zeta potential, FT-IR, XRD and SEM were made. The results prove that the intermolecular complexes formed between the polysaccharides and SDS can adsorb on the Mt. surface, change the structure of the electrical double layer and the stability properties of the studied suspensions. Graphical abstract: Unlabelled Image